2017
DOI: 10.1093/nar/gkx043
|View full text |Cite
|
Sign up to set email alerts
|

Anin vitrofluorescence based study of initiation of RNA synthesis by influenza B polymerase

Abstract: Influenza polymerase replicates, via a complementary RNA intermediate (cRNA), and transcribes the eight viral RNA (vRNA) genome segments. To initiate RNA synthesis it is bound to the conserved 5΄ and 3΄ extremities of the vRNA or cRNA (the ‘promoter’). 5΄-3΄ base-pairing in the distal promoter region is essential to position the template RNA at the polymerase active site, as shown by a new crystal structure with the 3΄ end threading through the template entry tunnel. We develop fluorescence polarization assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(93 citation statements)
references
References 56 publications
8
85
0
Order By: Relevance
“…Our results also show that in most complexes, the vRNA promoter is highly dynamic, exhibiting rapid transitions between different states. vRNA dynamics may therefore be a requirement for robust RNAP activity, as vRNA initiation complexes have been found to be ~200-fold more efficient in transcription initiation than cRNA initiation complexes (6). Intriguingly, this suggests that the rapid dynamics of the 3' vRNA may be the key to fast initiation, possibly because the dynamic nature of the vRNA promoter gives the 3ˈ RNA a greater chance of accessing the active site, and thus of being stabilized if nucleotides are present.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our results also show that in most complexes, the vRNA promoter is highly dynamic, exhibiting rapid transitions between different states. vRNA dynamics may therefore be a requirement for robust RNAP activity, as vRNA initiation complexes have been found to be ~200-fold more efficient in transcription initiation than cRNA initiation complexes (6). Intriguingly, this suggests that the rapid dynamics of the 3' vRNA may be the key to fast initiation, possibly because the dynamic nature of the vRNA promoter gives the 3ˈ RNA a greater chance of accessing the active site, and thus of being stabilized if nucleotides are present.…”
Section: Discussionmentioning
confidence: 99%
“…Crystal structures of the RNAP have shown that the vRNA 3ˈ end overshoots the active site by 1 nucleotide, meaning that for terminal initiation on the vRNA template to occur, the RNA needs to move back by one nucleotide (Fig. 5A) (6). Sequence comparison of the vRNA and cRNA promoters shows that the proximal 3ˈ cRNA is one nucleotide longer than the 3ˈ vRNA, and the distal promoter duplex region is one nucleotide shorter (compare Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations